Economic methods and legal reasoning - Towfigh, Emanuel; Petersen, Niels (Economic Methods for Lawyers, 2015)
The modern economic analysis of law was developed in the United States in the second half of the 20th century. There are several factors that contributed to this development. However, the main reason is probably a cultural one. The critique of legal realism with regard to the power of legal doctrine to determine the results of legal decisions has had a much stronger influence on legal academia in the United States than in continental Europe. With the disenchantment of legal doctrine, US scholars had to look for different fields of research activity. The economic analysis of law was one approach that tried to bridge this gap. The emergence of the Law and Economics movement in the US is often traced back to Ronald Coase’s article on ‘The Problem of Social Cost’ in the Journal of Law and Economics in 1960. This article paved the way for the economic analysis of tort and contract law. In the 1960s, Guido Calabresi advanced the economic analysis of tort law, culminating in his book on accident law in 1970. Gary Becker then applied economic principles to areas of law which had previously not been susceptible to an economic analysis: to crime, racial discrimination or family life. In 1973, Richard Posner published his seminal textbook on the Economic Analysis of Law, in which he tried to present for the first time a comprehensive analysis spanning several different fields of law.